1993
DOI: 10.1128/mcb.13.11.6889
|View full text |Cite
|
Sign up to set email alerts
|

Two signaling molecules share a phosphotyrosine-containing binding site in the platelet-derived growth factor receptor.

Abstract: (27,31). Recent studies indicate that binding of p85 to the tyrosinephosphorylated insulin receptor substrate 1 activates PI-3 kinase (2).SH2 domains are structural modules composed of approximately 100 amino acids (for reviews, see references 24, 30, and 35). SH2 domains have been identified in a wide range of molecules, which can be divided into two classes. One class contains proteins with enzymatic or other known functional elements and includes cytoplasmic tyrosine kinases such as the src product, PLC-y, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(129 citation statements)
references
References 46 publications
5
123
1
Order By: Relevance
“…The two other sites, Tyr579 and Tyr581 are located in the juxtamembrane domain of the b-receptor and have been shown to serve as binding sites for Src family kinases. It has been shown previously that signal transduction molecules may compete for binding to the same site on the PDGF b-receptor (Nishimura et al, 1993). In this context, it is noteworthy that v-Src has been described to associate with Stat3 in v-Src transformed cells and that Src is able to phosphorylate and activate Stat3 (Cao et al, 1996;Yu et al, 1995 (Figure 7 and data not shown), whereas no appreciable decrease in phosphorylation of Stat5 was seen in cells with Y771F or Y778F mutant receptors.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The two other sites, Tyr579 and Tyr581 are located in the juxtamembrane domain of the b-receptor and have been shown to serve as binding sites for Src family kinases. It has been shown previously that signal transduction molecules may compete for binding to the same site on the PDGF b-receptor (Nishimura et al, 1993). In this context, it is noteworthy that v-Src has been described to associate with Stat3 in v-Src transformed cells and that Src is able to phosphorylate and activate Stat3 (Cao et al, 1996;Yu et al, 1995 (Figure 7 and data not shown), whereas no appreciable decrease in phosphorylation of Stat5 was seen in cells with Y771F or Y778F mutant receptors.…”
Section: Discussionsupporting
confidence: 53%
“…Two autophosphorylation sites in the juxtamembrane domain (Tyr579 and Tyr581) mediate binding of Src family kinases (Mori et al, 1993). Autophosphorylation sites in the kinase insert bind Grb2 (Tyr716; Arvidsson et al, 1994), the regulatory subunit (p85) of phosphatidylinositol 3-kinase (Tyr740 and Tyr751; Fantl et al, 1992;Kashishian et al, 1992), Nck (Tyr751; Nishimura et al, 1993), and the GTPase-activating protein of Ras (Tyr771; Fantl et al, 1992;Kashishian et al, 1992). Two autophosphorylation sites in the C-terminal tail mediate binding of phospholipase C-g (Tyr1009 and Tyr1021; Kashishian and Cooper, 1993;RoÈ nnstrand et al, 1992;Valius et al, 1993), Tyr1009 in addition binds the tyrosine phosphatase SHP2 .…”
Section: Introductionmentioning
confidence: 99%
“…Following growth factor stimulation, Nck has been found in complexes with a number of phosphotyrosine proteins including the receptor tyrosine kinases Nishimura et al, 1993). However, except for the receptors, identity of the other Nck-associated phosphotyrosine proteins remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well established that Nck-1 can associate with several components of receptor tyrosine kinase-signaling pathways including EGF receptor (Li et al, 1992;Park and Rhee, 1992), PDGF receptor (Li et al, 1992;Nishimura et al, 1993), and IRS-1 (Lee et al, 1993) upon ligand activation. To test whether Nck-2 could recognize EGF receptors, we analyzed the ability of GST-Nck-2 (Figure 4, lane 1) to associate with EGF receptors from human A431 cells that were either serum starved or stimulated with EGF ( Figure 5).…”
Section: Association Of Nck-2 With Egf Receptor and Its Regulation Bymentioning
confidence: 99%